PENERAPAN USER CENTERED DESIGN (UCD) UNTUK SISTEM INFORMASI PERIJINAN PADA PT. ALFA GOLDLAND REALTY TANGERANG SELATAN - Ivo Grizelda; Wisti Dwi Septiani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
The basic necessities of human life besides clothing and food are boards or what is commonly known as a house. House made human as a shelter for the survival of life. Therefore, no doubt everyone wants a comfortable and safe house. If there is damage to the house, renovations or repairs must be done so that its function is still good and can continue to support a good life. PT. Alfa Goldland Realty is an estate management office that does business in the area of ​​integrated residential area providers. One of the activities carried out is to serve the application for building renovation permits. In its implementation before the house renovation is carried out, consumers must submit a renovation permit to the office of the manager. Licensing is one of the important aspects in public services and the regulation and control of the process that will be carried out. Constraints experienced by PT. Alfa Goldland Realty in the licensing service for submitting renovations is a lengthy, time-consuming procedure for one customer, giving rise to an image of inadequate service. Currently the staff handling the licensing process is still limited and inadequate with the many requests for renovation from consumers. Using the paper as a media in the renovation permit process makes the process less effective and efficient. The low quality of service that currently drives PT. Alfa Goldland Realty must immediately improve the quality of its services. The solution needed to PT. Alfa Goldland Realty is the implementation of information systems with the User Centered Design (UCD) method. This method is used for the design of information systems that are seen from the user or user side, so that user needs will be the basis of how the system is designed. The results of this study are web-based information systems that can be accessed by consumers and management offices for the licensing process so that the activities run more effectively and efficiently.